2017
DOI: 10.1175/jtech-d-16-0188.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Emissivity at Microwaves to Millimeter Waves over Polar Regions: Parameterization and Evaluation with Aircraft Experiments

Abstract: The Tool to Estimate Land Surface Emissivity from Microwave to Submillimeter Waves (TELSEM2) is linked to a climatology of monthly emissivity estimates and provides a parameterization of the surface emissivity up to 700 GHz, in the framework of the preparation for the Ice Cloud Imager (ICI) on board the Meteorological Operational Satellite Second Generation (MetOp-SG). It is an updated version of the Tool to Estimate Land Surface Emissivities at Microwave Frequencies (TELSEM; Aires et al. 2011). This study pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…self-similar Rayleigh-Gans Approximation (Hogan & Westbrook, 2014;Hogan et al, 2017) Aires et al, 2011;Wang et al, 2017) has been implemented, which provides the emissivities based on geographic location and month derived from satellite measurements.…”
Section: The Pamtra Modelmentioning
confidence: 99%
“…self-similar Rayleigh-Gans Approximation (Hogan & Westbrook, 2014;Hogan et al, 2017) Aires et al, 2011;Wang et al, 2017) has been implemented, which provides the emissivities based on geographic location and month derived from satellite measurements.…”
Section: The Pamtra Modelmentioning
confidence: 99%
“…It depends on the frequency, the incidence angle, and the subsurface extinction and reflections between snow and sea ice layers (Tonboe, 2010). Therefore, estimating the surface contribution is particularly complicated over sea ice due to the layering and the vertical structure of the snowpack, which affect the microwave emission processes (Mathew et al, 2008;Rosenkranz and Mätzler, 2008;Harlow, 2009Harlow, , 2011Tonboe, 2010;Tonboe et al, 2011), and to the large spatial and temporal variability of sea ice and snow cover (English, 2008;Tonboe et al, 2013;Wang et al, 2017). The understanding of the relationship between T eff and the physical temperature profile is complicated, especially at microwave frequencies ≥ 18 GHz, when scattering occurs, but it has been shown that from 6 to 50 GHz there is a high correlation between the T eff and the T Snow−Ice (Tonboe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Without adequate maps of surface emissivity from observations or near-real-time LSE models, the retrievals of precipitation over land will always be affected by substantial errors, especially when using MW channels whose weighting functions peak close to the ground. Several groups have been working on this problem, and datasets are available (e.g., [195][196][197]). LSE models also exist for use in NWP applications, and are useful also for precipitation retrievals; two examples are the Tool to Estimate Land-Surface Emissivities at Microwave frequencies (TELSEM) [198] and the Ringerud et al [199] model.…”
Section: Land Surface Emissionmentioning
confidence: 99%